2018
DOI: 10.1111/1759-7714.12620
|View full text |Cite
|
Sign up to set email alerts
|

Blind spot in lung cancer lymph node metastasis: Cross‐lobe peripheral lymph node metastasis in early stage patients

Abstract: BackgroundAt present, it has not yet been determined whether metastasis can be transferred cross‐lobe to peripheral lymph nodes (LNs) from other lobes in early stages of lung cancer, especially without any direct involvement to the pleura and parenchyma of the lobe. This study was conducted to investigate this issue.MethodsA retrospective analysis was conducted at the Chinese Academy of Medical Sciences. Patients undergoing right middle and lower lobectomy with lymphadenectomy for preoperative clinical stage I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
3
6
0
Order By: Relevance
“…This study retrospectively investigated the prevalence and risk factors of lobar lymph node metastasis from NTBL in patients with NSCLC. In our study, NTBL lobar lymph nodes were involved in 12.6% of patients, which is consistent with the published results, ranging from 6.5 to 13.2% [ 11 , 14 , 15 , 21 ]. A higher proportion of adenocarcinomas were observed in the positive NTBL group compared to the negative NTBL group.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This study retrospectively investigated the prevalence and risk factors of lobar lymph node metastasis from NTBL in patients with NSCLC. In our study, NTBL lobar lymph nodes were involved in 12.6% of patients, which is consistent with the published results, ranging from 6.5 to 13.2% [ 11 , 14 , 15 , 21 ]. A higher proportion of adenocarcinomas were observed in the positive NTBL group compared to the negative NTBL group.…”
Section: Discussionsupporting
confidence: 93%
“…Given the retrospective design, some selection bias could not be avoided: the percentage of metastatic N1 and N2 patients was more than that of other studies [ 11 , 14 ]; this retrospective study was carried out in a single center with a limited number of enrolled patients. But the rate of aberrant lymph node metastases to NTBL was 12.6% (38 out of 301 patients), which is consistent with the published results, ranging from 6.5% to 13.2% [ 11 , 14 , 15 , 21 ]. Besides, there is no significant difference between 301 enrolled patients with the excluded 40 patients who performed extended NTBL lymph node dissection but missed pathology diagnosis, in terms of demographic information such as sex and age ( S5 Table ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The present study found that 15 (12.7%) patients had lymph node metastases in NTBL and 9 had metastases in N2 sites. As reported in the literature, [24] whether or not LN metastases occurred in NTBL did not affect staging or treatment. We demonstrated a significantly higher frequency of lymph node metastases in NTBL among tumors invading across complete fissures and in tumors sized 3.0 cm or more in diameter.…”
Section: Discussionmentioning
confidence: 69%